Does Government Assistance Increase the Yield of Food Crops in Indonesia? - Prasetyo, Octavia Rizky; Kadir, Kadir (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2024)
Government assistance has been deployed to help food crop farmers enhance their yields. However, to our knowledge, studies assessing the impact of government assistance on food crop yield using a dedicated nationwide survey in the context of Indonesia are not available yet. Thus, our study aims to contribute to the literature by assessing the impact of government assistance (fertilizers, seeds, and agricultural tools and machinery) on food crops yield using the results of the 2018 and 2021 Crop Cutting Survey conducted by BPS. By applying multinomial logistic regression, we found that the fertilizers and seeds assistance significantly lower the chance of food crop farmers experiencing lower yield, provided that the distribution is on-time and suitable with the need of farmers. In contrast, our findings indicate that the benefit of tools and machinery assistance in enhancing food crop yield has not been optimized. The study recommends a more targeted distribution of tools and machinery assistance by taking into account farmers’ needs, cultivation characteristics, and support for the maintenance and management.